A Stochastic Approach to Generalized Modularity Based Community Detection - James Tipton; Jordan Langston (Entropy, 2025)
We study a stochastic approach to generalized modularity-based community detection by comparing two variants of the aforementioned approach to the standard modularity-based approach. In particular, we compare means and distributions. We also confirm that the stochastic approach can outperform standard modularity approaches.